(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. This article discusses the possibility of extracting vanadium pentoxide from mineral and industrial raw materials. Based on the study of this topic and the analysis of the results of the studies, the author came to the conclusion that medium temperature roasting of the ore is carried out by vanadium water-soluble sodium vanadate (NaVO3) and the subsequent leaching of the metal using sulfuric acid increases the vanadium extraction 76,5 to 90,2%. It was also revealed that in the process of firing vanadium as a binder material, the most effective reagent is technical soda. It was found that the solubility of sodium vanadate is more effective than the sulfuric acid medium than conventional aqueous leaching of the product. Nevertheless, a special combined technology of selective sintering and leaching of the cinder has been determined and worked out: the selective deposition of vanadium and its separation from unnecessary impurities and the calcination of the precipitate bring a high-frequency production of V2O5 of 98-99%.